2014
DOI: 10.9753/icce.v34.management.10
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Risk Assessment at Isla Del Carmen and Cancun, Mexico

Abstract: Tropical cyclones and Cold-Fronts lead to storm surge and wave hazards annually in the coastal zones of the Gulf of Mexico and Caribbean Sea. Anthropogenic intervention over a wide extension of these coasts has affected their natural equilibrium and resilience to these extreme natural phenomena. An integrated risk analysis is presented here, which aims to prevent or reduce serious beach erosion damage and inundation of settlements next to these beaches. Two important coastal lagoon barriers in Mexico were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…In Quintana Roo, uncontrolled and intense coastal development since the 1970s, particularly in Cancun, Cozumel, Isla Mujeres, Playa del Carmen and along the Mayan Riviera (Cancun to Tulum coastal stretch), have altered the natural coastal system and hence the resilience to extreme natural phenomena (Escudero-Castillo et al, 2014a). The area is also exposed to hurricanes and storms that produce recurrent flooding and erosion of settlements and assets on the beach front (Escudero-Castillo et al, 2014a;Mendoza et al, 2015), while anthropogenic interventions and degradation of ecosystems over wide extensions of these coasts have also driven chronic erosion and increased vulnerability to extreme weather events that put the people and the state's economy at risk (Escudero-Castillo et al, 2014a. However, the MAR is increasingly threatened by pollution, storm damage, ocean acidification, rising sea surface temperatures, disease outbreaks and unsustainable management practices (Mcfield et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Quintana Roo, uncontrolled and intense coastal development since the 1970s, particularly in Cancun, Cozumel, Isla Mujeres, Playa del Carmen and along the Mayan Riviera (Cancun to Tulum coastal stretch), have altered the natural coastal system and hence the resilience to extreme natural phenomena (Escudero-Castillo et al, 2014a). The area is also exposed to hurricanes and storms that produce recurrent flooding and erosion of settlements and assets on the beach front (Escudero-Castillo et al, 2014a;Mendoza et al, 2015), while anthropogenic interventions and degradation of ecosystems over wide extensions of these coasts have also driven chronic erosion and increased vulnerability to extreme weather events that put the people and the state's economy at risk (Escudero-Castillo et al, 2014a. However, the MAR is increasingly threatened by pollution, storm damage, ocean acidification, rising sea surface temperatures, disease outbreaks and unsustainable management practices (Mcfield et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the concentration of urban development in these areas, coastal populations are expected to continue to increase, leading to new infrastructure and higher potential costs due to coastal storm events. These costs include tangible and intangible losses, such as physical damage to infrastructure, ecosystem loss and degradation, business and social disruptions and loss of life (Donnelly et al, 2006;Escudero et al, 2014;Kraus and Wamsley, 2003). Smith et al (2015) have shown that, in the U.S. from 1980 to 2014, 50% of the direct economic damage caused by natural disasters were due to tropical cyclones.…”
Section: Introductionmentioning
confidence: 99%